Incorporation of randomized controlled trials into organizational guidelines for obstetricians and gynecologists. (April 2022) - Gutierrez, Rigoberto; Bicocca, Matthew; Opara, Gregory; Gupta, Megha; Bartal, Michal Fishel; Chauhan, Suneet P.; Wagner, Stephen
Abstract: Background: The American College of Obstetricians and Gynecologists publishes practice bulletins and committee opinions to serve as clinical guidelines for physicians. The objective of this study was to quantify the frequency that randomized controlled trials become incorporated into the American College of Obstetricians and Gynecologists documents (either practice bulletins or committee opinions). Methods: Original research articles published in The American Journal of Obstetrics and Gynecology, The Journal of the American Medical Association, The New England Journal of Medicine, and Obstetrics and Gynecology between 2009 and 2014 were examined and randomized controlled trials (RCT) in obstetrics and gynecology were identified. Adjusted odds ratio (aOR) with 95% confidence intervals (CI) were calculated to examine the factors associated with a citable RCT being referenced versus not in ACOG documents. Results: Of the 306 randomized controlled trials identified 248 (81.0%) met the inclusion criteria, with 128 (51.6%) of eligible RCT being cited The factors which increased the likelihood of a RCT being referenced, versus not being, were: if device or surgery was the intervention (aOR 3.60; 95% CI 1.85–7.00) and if the sample size of the trial was 500–999 (aOR 3.70 (1.39–9.82). The following factors were not associated with whether the RCT was or was not referenced in the ACOG documents: topic was obstetric or gynecologic, the trial was conducted in the US or abroad, multi- or single center, year of publication and the journal. Conclusion: Since about half of the citable randomized controlled trials published in obstetrics and gynecology are incorporated into ACOG practice bulletins and committee opinions a greater transparency is warranted as to why RCTs are or are not referenced.